Changing the E-Waste Management Paradigm: an Innovative Approach with the Electronic Waste-Atm System - Hakim, Luqman (IDFoS Indonesia, 2024)
Handling electronic waste (e-waste) is one of the crucial environmental challenges in today's digital age. With the rapid growth of electronic device usage, the volume of e-waste generated continues to increase, posing significant risks to the environment and human health if not managed properly. One innovative solution that has emerged is the development of the